The effect of loading speed on the force frequency spectrum during eccentric & concentric calf exercise. Issue 2 (20th January 2011) - Chaudhry, S; Screen, H R C; Woledge, R C; Bader, D; Morrissey, D
Abstract : Introduction: Heavy load eccentric training (ET) has been shown to be more effective than concentric training (CT) in treating Achilles tendinopathy.1 2 It is unclear at what speed ET should be performed to treat the condition with greatest efficacy. Recent studies have indicated that high frequency tendon force fluctuations may underpin therapeutic mechanotransduction, but the effect of training speed on resulting tendon vibration remains unexplored. The aim of this study was to compare tendon vibration during ET and CT at three speeds commonly employed during conservative treatment. Methods: 24 healthy volunteers (12 male and 12 female, age=27.8±1.9 years) performed ET and CT exercises for the Achilles tendon either at a fast (loading phase=1.5 s), medium (loading phase=3 s) or slow pace (loading phase=6 s). Tendon vibration was measured by analysing the power spectra of the ground reaction force vector using a fast Fourier transform with 1Hz windows, and compared using ANOVA. Results: High frequency vibrations (8–13 Hz range) were greatest during fast and medium speed ET, with a mean of 15.8 N 2 /Hz (sd=8.8). This was significantly greater than all other combinations of conditions and speeds (p value range across these frequencies=0.03–0.001). No significant differences between any combinations of speed and loading condition were found in the 1–7 Hz low frequency range (p value range=0.11–0.98). Conclusion: The observed high frequency Achilles tendon force fluctuations during fast and medium speed ET were mostly in the higher frequency range, reflecting where physiological tremor particularly occurs. This may reflect inefficient recruitment of large motor units at high speeds, creating oscillation frequencies that are known to stimulate mechanotransduction in tenocytes. These findings were made in normal subjects and pave the way for exploration in patients with tendinopathic disease.